Women at Greater Sexual Risk for STIs/HIV Have a Lower Mesolimbic and Affective Bias Response to Sexual Stimuli - Regier, Paul S.; Teitelman, Anne M.; Jagannathan, Kanchana; Monge, Zachary A.; McCondochie, Calumina; Elkind, Jaclynn; Childress, Anna Rose (Frontiers in Behavioral Neuroscience, 2020)
Young adult women in the United States have high rates of sexually transmitted infections, increasing the risk of HIV. The underlying neurobiology of behaviors that increase the probability of contracting STIs and HIV is just beginning to be explored. The current study assessed the link between sexual risk and the brain and behavioral response to sexual cues in emerging adult women. Our hypothesis was that women with more activity in reward/motivational circuitry would report higher sexual risk behaviors and would evidence higher positive affective bias to visual sexual stimuli. Women (n = 52; age = 18-24 years) who had protected sex 100% of the time (n=17) vs. those who did not (n=34), in the past three months, were compared on their brain response to 500 msec evocative (sex, aversive, food) vs. neutral cues in a BOLD fMRI fast event-related design. Based on existing literature, an a priori anatomical “cue-reactive” mask was used to constrain the analyses. Self-reported sexual activity and the affective bias scores to sexual cues were examined as correlates with the brain response to cues. In contrast to our initial hypothesis, the higher sexual risk (Unprotected) group had significantly less activation in mesolimbic brain regions and lower (less positive) affective bias scores to sexual cues compared to the lower risk (Protected) group. As predicted, the brain response was positively correlated with sexual bias. Follow-up analyses showed an effect of partner “risk” (e.g., more vs. less knowledge of partner’s STIs/HIV status). This evidence suggests that women who have protected sex may view sexual-related stimuli more positively, reflected by a neural response in reward/motivational regions and more positive sexual bias scores. In contrast, young women who have a lower mesolimbic response to sexual cues and who feel more negatively about sexual-related stimuli may be at increased risk for STIs/HIV. This data may help identify young women who are at greatest risk for acquiring STIs and/or HIV, which carries added importance with the availability of new medications that can prevent HIV.